Legislative history of the International Criminal Court Volume I - Bassiouni, M. Cherif, 1937-2017; Schabas, William, 1950- (Leiden ; Boston : Brill Nijhoff, 2016)
"This unique work is an article-by-article drafting history of the ICC Statute containing all versions of every article in the Statute as it evolved from 1994 to 1998. It also integrates in the Statute's provisions the "Elements of the Crimes" and the "Rules of Procedure and Evidence" adopted by the Preparatory Commission (1998-2000) and the Regulations of the Court adopted by the plenary of judges. A description of the ICC mechanisms and institutions precedes this article-by-article legislative history. Other relevant documents are also included, such as those concerning the privileges and immunities and financial regulations of the Court, as well as its relationship with the United Nations. This new edition contains the amendments adopted at the Kampala Conference, amendments to the Rules of Procedure and Evidence and the Regulations of the Court, and references to relevant case law covering the first decade of the Court's judicial activity. It also offers an insightful first-hand account of the drafting process both prior to and during the Rome Diplomatic Conference, along with a detailed historical survey of the efforts to establish the ICC"--Back cover.
Volume 2: [An Article-by-Article Evolution of the Statute from 1994--2015] -- Explanatory Note on the Integrated Legislative Text -- Drafts of the ICC Statute. Introduction; Preamble; Part 1. Establishment of the Court (Articles 1--4); Part 2. Jurisdiction, admissibility and applicable law (Articles 5--21); Part 3. General principles of criminal law (Articles 22--33); Part 4. Composition and administration of the Court (Articles 34--52); Part 5. Investigation and prosecution (Articles 53--61); Part 6. The trial (Articles 62--76); Part 7. Penalties (Articles 77--80); Part 8. Appeal and revision (Articles 81--85); Part 9. International cooperation and judicial assistance (Articles 86--102); Part 10. Enforcement (Articles 103--111); Part 11. Assembly of state parties (Article 112); Part 12. Financial (Articles 113--118); Part 13. Final clauses (Articles 119--128).
Includes bibliographical references and indexes.
Keywords: International Criminal Court -- History; Rome Statute of the International Criminal Court -- (1998 July 17); International criminal courts -- Legislative history; Legislative histories